2009
DOI: 10.1116/1.3106625
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapor deposition of WNxCy using the tungsten piperidylhydrazido complex Cl4(CH3CN)W(N-pip): Deposition, characterization, and diffusion barrier evaluation

Abstract: The tungsten piperidylhydrazido complex Cl 4 ͑CH 3 CN͒W͑N-pip͒ ͑1͒ was used for film growth of tungsten carbonitride ͑WN x C y ͒ by metal-organic chemical vapor deposition ͑CVD͒ in the absence and presence of ammonia ͑NH 3 ͒ in H 2 carrier. The microstructure of films deposited with NH 3 was x-ray amorphous between 300 and 450°C. The chemical composition of films deposited with NH 3 exhibited increased N levels and decreased C levels over the entire deposition temperature range ͑300-700°C͒ as compared to films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The film obtained at 850 °C has a particularly high C/W ratio. We speculate that the film contains amorphous carbon (a-C), similar to a previously reported WNxCy film formed at a high temperature by aerosol-assisted CVD [32]. The columnar structure seen in the SEM image of the film obtained at 850 °C (Fig.…”
Section: Composition and Morphologysupporting
confidence: 86%
“…The film obtained at 850 °C has a particularly high C/W ratio. We speculate that the film contains amorphous carbon (a-C), similar to a previously reported WNxCy film formed at a high temperature by aerosol-assisted CVD [32]. The columnar structure seen in the SEM image of the film obtained at 850 °C (Fig.…”
Section: Composition and Morphologysupporting
confidence: 86%
“…For N-doped MoS 2 , S-bound ligands from prior single-source precursors for MoS 2 could be used in combination with a nitrogen source, most likely from N-bound ligands. Nitrogen-coordinated ligands such as imido, nitrido, amido, , amidinato, and hydrazido , moieties have been used as sources of nitrogen in depositions of metal nitride and carbonitride films. These ligands could also serve as nitrogen sources for N-MoS 2 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…33 Similar WN x C y films (grown in the same reactor under similar conditions) exhibited resistivities between 225 μ -cm and 87 m -cm, although typically less than 5000 μ -cm. 15,19,34 It was shown that both an increase of C and decrease of N incorporation in the W sub-lattice can lower film resistivity; however there also exists interplay between grain size, grain boundary density, crystallinity, film density, elemental composition and valence states, as well as film thickness. Below 200 • C, O incorporation is prominent and is most likely due to background oxygen and water vapor in the deposition chamber, as well as the low film density, which could accommodate significant post-growth oxygen incorporation.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, these complexes include nitrogen-bound moieties such as amido, imido, hydrazido, amidinate or guanidinate ligands, 13,14 and have been used in single-source or NH 3 /H 2 co-reacting conditions to deposit WN x . Unfortunately, many of these precursors still require relatively high deposition temperature (>350 • C) [15][16][17][18][19][20][21][22] that can compromise contact level structures 2,23 and neighboring dielectrics. 24 In addition, the development of ultra-low temperature CVD WN x C y has potential application to flexible and organic devices.…”
mentioning
confidence: 99%